Influence of a field hamstring eccentric training on muscle strength and flexibility - Delvaux, F.; Schwartz, C.; Decréquy, T.; Devalckeneer, T.; Paulus, J.; Bornheim, S.; Kaux, J.-F.; Croisier, J.-L. (International Journal of Sports Medicine, 2020)
Muscle strength imbalances and poor flexibility are frequently described as risk factors for hamstring injury. Preventive strategies include eccentric exercises, but the influence of field eccentric exercises on these risk factors remains unclear. We investigated the influence of a field hamstring eccentric program on hamstring strength and flexibility. Twenty-seven amateur athletes were randomly assigned to an intervention (n=13) or control group (n=14). In the intervention group, participants were involved in 15 sessions of four eccentric exercises. Peak torque, hamstring-to-quadriceps ratios, passive and active flexibility were analyzed. No significant modifications of strength, passive or active flexibility were observed in the control group (p>0.05). Hamstring eccentric peak torque (+7.1%) and functional hamstring-to-quadriceps ratios (9.3%) were significantly increased (p<0.05) in the intervention group, but not concentric strength (p<0.05). Passive straight leg raise was significantly increased by 11.4° (+12.7%, p<0.001), but not active flexibility (+3.1%, p>0.05). In conclusion, a 6-week eccentric program, including four field exercises for hamstring muscles, is an effective method of improving eccentric strength, functional ratios and, especially, passive flexibility. As this program may be easily implemented in a real-world context, this association of multiple eccentric exercises might be useful in an injury prevention strategy.